2022
DOI: 10.18006/2022.10(3).533.538
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Respiratory Symptoms and Associated Risk Factors among Street Food Vendors in Klang Valley, Malaysia

Abstract: The street vendors in Malaysia are at an increased risk of developing respiratory symptoms owing to the continuous exposure to road dust, vehicle emissions, extreme weather conditions, and air pollutants from industrial sites. Hence, the current study aimed to establish the prevalence of respiratory symptoms and the risk factors associated with it among street food vendors in Klang Valley, Malaysia through a cross-sectional study among 237 street food vendors. The socio-demographic data, work characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…The PM exposure in comparison to meteorological conditions showed that spring and winter recorded higher exposures as compared to summer and autumn. These findings were consistent with several international studies [ 20 , 21 , 22 ]. Open-fire-usage markets have higher exposure levels, which increase the possibility of respiratory, cardiovascular, and reproductive system disorders [ 20 , 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The PM exposure in comparison to meteorological conditions showed that spring and winter recorded higher exposures as compared to summer and autumn. These findings were consistent with several international studies [ 20 , 21 , 22 ]. Open-fire-usage markets have higher exposure levels, which increase the possibility of respiratory, cardiovascular, and reproductive system disorders [ 20 , 21 , 22 , 23 ].…”
Section: Resultssupporting
confidence: 94%
“…These findings were consistent with several international studies [ 20 , 21 , 22 ]. Open-fire-usage markets have higher exposure levels, which increase the possibility of respiratory, cardiovascular, and reproductive system disorders [ 20 , 21 , 22 , 23 ]. This study’s findings also showed that there was the usage of incorrect respiratory protective equipment (RPE) (surgical and cloth masks) for the indicated air contaminants which may be ineffective in this trade [ 24 ].…”
Section: Resultssupporting
confidence: 94%
“…As a result, people in this age group are more likely to use alternative economic options to the formal economy. Furthermore, the age range is consistent with other studies on street vendors, which found that a significant proportion of their respondents fell within a similar age range [2][3][4][5][6][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 86%
“…The study's predominance of female food vendors (55%) is not surprising, as numerous studies have shown that female vendors, particularly in food vending, are the majority [2][3][4][5][6][11][12][13][14][15]. The majority of vendors were between 30 and 39 years; unemployment rates in this age range of 30 to 44 years are typically high [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation